Evaluation of Nonthermal Technologies to Reduce or Replace Nitrite in Meat Products - Andrade, Bruna Fernandes; Carmo, Lorrany Ramos do; Tanaka, Marcelo Stefani; Torres Filho, Robledo de Almeida; Ramos, Alcinéia de Lemos Souza; Ramos, Eduardo Mendes (Food technology and biotechnology, 2025)
Nitrite and nitrate salts are preservatives that act as antimicrobial (bacteriostatic and bactericidal activity) and antioxidant agents in the processing of meat products and confer sensory properties to meat (by creating and preserving colours and flavours). Nitrite is mainly used as a preservative to prevent the growth of Clostridium botulinum and the production of its toxins. However, nitrite and nitrate are also associated with the production of N-nitroso compounds, such as carcinogenic N-nitrosamines, which can have adverse health effects. Therefore, the health risks of these preservatives must be weighed against the need to prevent foodborne pathogens, especially spores of C. botulinum, from infecting food. In this review, we discuss the advantages and disadvantages of using nonthermal technologies as a strategy to partially or totally replace nitrite in meat products, particularly regarding antimicrobial efficacy and N-nitrosamine formation. Methods such as high-pressure processing, pulsed electric fields and cold plasma have been studied for these purposes, but these technologies can alter the sensory properties and stability of foods. Nevertheless, irradiation at lower doses has great potential as a tool for reformulation of cured meat products. It contributes to the reduction of the residual nitrite and consequently to the production of N-nitrosamines while ensuring microbiological safety without significant changes in the product quality.